2019
DOI: 10.1002/ijc.32595
|View full text |Cite
|
Sign up to set email alerts
|

Blood arsenic levels and the risk of familial breast cancer in Poland

Abstract: Arsenic is recognized as a potent carcinogen at high concentrations, but the relationship between environmental arsenic and breast cancer risk has not well been studied. Most research has focused on the effect of arsenic in populations with high endemic exposure, and not in populations with arsenic levels within normal limits. We sought to determine if blood arsenic levels predict the risk of breast and other cancers risk among women in northern Poland. The cohort consisted of 1,702 healthy women, aged 40 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Previously, very high arsenic concentration in the blood samples of the cancer patients was reported by. 26,35 The hair and the toenail samples relatively had very high arsenic concentration in hair samples (1296•9μg/Kg) while in toenail samples, as high as 621•83μg/Kg was recorded. This was signi cantly higher than the control samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, very high arsenic concentration in the blood samples of the cancer patients was reported by. 26,35 The hair and the toenail samples relatively had very high arsenic concentration in hair samples (1296•9μg/Kg) while in toenail samples, as high as 621•83μg/Kg was recorded. This was signi cantly higher than the control samples.…”
Section: Discussionmentioning
confidence: 99%
“…46 At the genetic level, mutations in CHEK2, PALB2, NBN, BRCA1 and other susceptible genes have been found to be mutated due to metal toxicity. [47][48][49] Marciniak et al, (2020), 35 have evaluated the arsenic exposure with 13 folds risk of breast cancer in the exposed population. The study also correlates the blood arsenic levels with the breast cancer risk in women.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic may also be found in vegetables, legumes, nuts and fruits. In a large cohort study of 1702 Polish women, Marciniak et al [ 57 ] found that chronic low-level exposure to arsenic compounds may lead to a 13-fold increase in breast cancer. The potential mechanism by which arsenic may influence breast cancer development includes estrogen receptor function disruption and estrogen signaling pathway suppression [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were taken from patients’ pre-treatment at the time of diagnosis. Total arsenic concentration in their blood was measured by the inductively coupled plasma mass spectrometer method reported in our previous study [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Biomolecular mechanisms of As clearance are still poorly understood, however there are some theories that its biotransformation may exert carcinogenesis in both a genotoxic and non-genotoxic manner [ 15 , 16 ]. Recently we have been able to show that As is a major cancer risk factor for women in Poland–high levels of blood As (the highest quartile) is associated with more than 10-times higher risk of breast cancers as compared to quartile with the lowest As levels [ 17 ]. The above correlations have not been observed in our studies of men (data not shown).…”
Section: Introductionmentioning
confidence: 99%